2007
DOI: 10.1194/jlr.m700055-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Feedback activation of ferrous 5-lipoxygenase during leukotriene synthesis by coexisting linoleic acid

Abstract: Ferrous lipoxygenases seem to be activated through a feedback control mechanism via FA hydroperoxides generated from PUFAs by partially existing ferric lipoxygenases. However, during leukotriene synthesis, feedback activation of ferrous 5-lipoxygenase in the presence of arachidonic acid (AA) was not observed. In the present study, we examined the feedback activation of ferrous 5-lipoxygenase in the 5-lipoxygenase/AA system in the presence of linoleic aicd (LA), which is a predominant component of membrane phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Radical Spin Trapping Adducts-To investigate the formation of a carbon-centered radical at C-8 (15), we used the method of Koshiishi and co-workers (33)(34)(35) to scavenge the hypothetical C-8 radical with the radical scavenger Cm⌬P. In this case, a nitroxyl radical competes with the oxygen molecule for the lipid allyl radical on the enzyme, resulting in the formation of a lipid allyl radical-Cm⌬P adduct that can be detected by mass spectrometry.…”
Section: Analysis Of Product Formation In the Presencementioning
confidence: 99%
“…Radical Spin Trapping Adducts-To investigate the formation of a carbon-centered radical at C-8 (15), we used the method of Koshiishi and co-workers (33)(34)(35) to scavenge the hypothetical C-8 radical with the radical scavenger Cm⌬P. In this case, a nitroxyl radical competes with the oxygen molecule for the lipid allyl radical on the enzyme, resulting in the formation of a lipid allyl radical-Cm⌬P adduct that can be detected by mass spectrometry.…”
Section: Analysis Of Product Formation In the Presencementioning
confidence: 99%
“…In the present study, we employed soybean 15-lipoxygenase to establish the evaluation method for scavenging effi ciency against a fatty acid allyl radical on the lipoxygenase. In our previous study (Takajo et al, 2007b), we demonstrated that a nitroxyl radical can trap a fatty acid allyl radical in rabbit reticulocyte 12/15-lipoxygenase and potato 5-lipoxygenase as well as soybean 15-lipoxygenase at lower oxygen content. Namely, the fatty acid allyl radical on the enzyme is a common target for inactivation of these lipoxygenase isozymes.…”
Section: Resultsmentioning
confidence: 85%
“…[4][5][6][7] In this pseudoperoxidase reaction, ferrous lipoxygenase donates one electron to fatty acid hydroperoxide, producing fatty acid alkoxyl radical through cleavage of the O-O bond. [8][9][10][11][12] Even though the fate of the fatty acid alkoxyl radical remains obscure, it seems reasonable to assume that the fatty acid alkoxyl radical is converted to oxo-fatty acid by one-electron oxidation. In the lipoxygenase/ polyunsaturated fatty acid system, one-electron oxidation of fatty acid alkoxyl radical is thought to be coupled with oneelectron reduction of a free radical by radical-radical dismutation (R(-H)-O• + R′• R = O + R′-H).…”
Section: Introductionmentioning
confidence: 99%